On Proof Complexity of Some Type of Tautologies - Altunyan, Vahagn N.; Petrosyan, Garik V. (Изд-во НАН РА)
In this paper, we investigate the proof complexities of a special type of tautologies,which are described as tautologies consisting of implications and literals. In particular,we prove that the proof of this kind of tautologies can be polynomially reduced to theproof of tautologies consisting of formulas that are described by sign-alternating trees.
Keywords: Mathematical cybernetics; Computer science